(untitled) (Journal of Science and Technology Research, 2024)
The jute fibre (JF) reinforced polyethylene (PE), polypropylene (PP), and epoxy resin (ER) matrix composites were developed. The JF content was maintained to 30% by weight. Then tensile properties and impact strength were measured. The finest tensile properties were found for JF/PP composites. The tensile strength (TS), tensile modulus (TM), elongation at break (Eb%), and impact strength (IS) of the JF/PP composites were found to be 38.00 MPa, 1800 MPa, 12%, and 8.20 kJ/m2 respectively. The bonds between JF and polymers of the developed composites were investigated and found good adhesion. The composite samples were exposed to gamma ray and it was found that gamma radiation have the potential to improve the tensile and impact strength of the JF-based polymer composites. The JF content polymer-based decorative composites were also developed. The outcomes of this investigation showed a minor decrease of the tensile and impact strength of the composites but enhanced the beauty of the composites noticeably. The developed JF/polymer composites have sufficient mechanical strength for many applications pretty. J. of Sci. and Tech. Res. 5(1): 75-82, 2023